Comparative study between POMPP score versus Boey score to predict morbidity and mortality in peptic perforation peritonitis - K. R., Bhanu Prakash; Patil, Subhas; Mohan, Manasa (International Surgery Journal, 2021)
Background: Peptic ulcer disease (PUD) results from an imbalance between stomach acid-pepsin and mucosal defense barriers. It affects 4 million people worldwide annually. Peptic ulcer perforation is one of the most common surgical emergencies and is associated with a high rate of morbidity and mortality. This is due to presence of various risk factors among the population like H. pylori infection, long term NSAID use, alcohol ingestion, smoking and steroid use. Peptic ulcer perforation peritonitis usually requires an emergency surgical intervention and hence the need for this study, to compare POMPP and Boey scores as predictors of morbidity and mortality in patients with peptic perforation peritonitis. Methods: This prospective observational study was conducted in the hospitals attached to Bangalore Medical College and Research Institute from November 2018 to May 2020. All patients above 18 years with features of hollow viscus perforation with per-operative finding of perforated peptic ulcer were included in the study. Patients with histopathology suggestive of malignancy were excluded. Results: A total of 65 patients were included in the study. On analysis of the data by Chi-square test, P value of both POMPP and Boey scores was found to be <0.05 which is statistically significant. The most important predictive factors of mortality and morbidity were duration of perforation >24 hours, age >65 years and pre-operative shock. Conclusions: Both scoring systems are easy to use and can assist in accurate and early identification of high-risk patients and are important in predicting mortality and morbidity in patients with peptic ulcer perforation.